Novel Imaging and Spectroscopy - Yang, Jinfeng; Yang, Jinfeng (IntechOpen, 2020)
Imaging and spectroscopy are the most important and challenging techniques for not only research on materials science, chemistry, and biology, but also medical diagnoses. In this book, we have collected information on several novel imaging and spectroscopic techniques, including time-resolved electron diffraction/microscopy for materials science, various spectroscopes for physics and chemistry, and high-resolution computed tomography for medical science. We think that the content in each chapter is impressive and we hope this book will contribute to future instrument developments and new applications.
English
Keywords: Applied physics; Applied physics